Downregulation of and Gene Expression by Some Antioxidants in Rats Under Sodium Nitrite-Induced Hypoxic Stress - Laila Mohamed Fadda; Hala A. Attia; Nouf Mohamed Al-Rasheed; Hanaa Mahmoud Ali; Nawal Mohamed Al-Rasheed (SAGE Publishing, 2018)
This study assessed the effect of L-arginine (L-argin), carnosine (carno), or their combination in the amelioration of certain biochemical indices induced in the liver of hypoxic rats. Hypoxia was induced via sodium nitrite (S.nit) injection at a dose of 75 mg/kg. Rats were administered L-argin (250 mg/kg) or carno (250 mg/kg), either alone or in combination, 24 hours and 1 hour prior to S.nit intoxication. Hypoxia significantly elevated serum alanine aminotransferase, in addition to a significant upregulation of hepatic heat shock protein 70 with concurrent reduction in the level of vascular endothelial growth factor. Moreover, hepatic vascular endothelial growth factor 1 (flt-1), hypoxia inducible factor-1α gene expression, and cytochrome P450 levels were elevated, compared with the normoxic group. The antioxidants, administered either alone or in combination, markedly downregulated all of the previously mentioned biomarkers, compared to the hypoxic rats. Histopathological examination revealed hepatocellular degeneration and nuclear pyknosis, in addition to inflammatory cellular infiltration in the hypoxic rats, whereas treatment with the studied antioxidants improved the liver architecture. The present data revealed the efficacy of L-argin and carno in ameliorating the hepatic damage induced via angiogenic markers in response to hypoxia, the combination regimen showing the superior effect.